Brief analysis of the development characteristics and deformation mechanism of ground fissures on the MH Highway in the Ethiopian Rift Valley - Liu, Weimin; Xu, Cheng; Huang, Xiaonian (Frontiers in Earth Science, 2023)
Ground fissures are widely developed in the Ethiopian Rift Valley, posing a major threat to the construction of the proposed Modjo−Hawassa (MH) Highway. The development characteristics, distribution, and communication law of ground fissures along the highway are studied using the comprehensive investigation method and technology. On this basis, the deformation mechanism and evolution of ground fissures are analyzed, which can provide geological support for the prevention and control of highway cracks in the area where ground fissures are developed.